Ultra-thin caliber endoscopes in daily practice: uses for therapeutic application and beyond on the basis of review of 1028 procedures - Oterdoom, Leendert H.; Goet, Jorn C.; Jacobs, Maarten A. J. M.; Mulder, Chris J. J. (Endoscopy International Open, 2015)
Background and study aims: Ultra-thin caliber endoscopes (UTCEs) are versatile and applicable in various conditions. However, only limited data exist on the actual daily clinical use of UTCEs. The aim of our study was to determine indications for UTCEs in a large patient cohort. In turn, our 2 main objectives were (1) to evaluate patient comfort and safety and (2) to determine benefits and potential advantages associated with the use of UTCEs in this same cohort.Patients and methods: We performed a retrospective analysis of our prospective database of 1028 procedures with UTCEs in 457 patients. All procedures were carried out in the Department of Gastroenterology and Hepatology, VU University Medical Center, in Amsterdam, the Netherlands, between May 2008 and May 2014. In these procedures, either the Fujinon (Tokyo, Japan) EG-530N UTCE or the Olympus (Tokyo, Japan) GIF N-180 UTCE was used.Results: Mean (standard deviation [SD]) age of patients was 64 (20) years, and most (60 %) of the patients were men. Most (61 %) of the underlying diseases, requiring endoscopic procedures, were found in the esophagus. Of the procedures performed, 91 % were successful, and 82 % were therapeutic. In comparison with regular endoscopes, the most important advantage of the UTCE was the ability to pass a stenosis (37 %), followed by nasogastric feeding tube placement (13 %). Newer and more innovative uses of the UTCE were percutaneous endoscopic gastrostomy (PEG)-jejunal extension placement with endoscope introduction through existing PEG tract, retrograde esophageal introduction through existing PEG tract, inspection of colonic neovagina stenosis, and direct inspection of the common bile duct.Conclusions: In everyday clinical practice, the UTCE has specific advantages over conventional endoscopes because of its small caliber. The 3 main advantages are (1) introduction of high-grade strictures; (2) introduction of fistulas, including PEG fistula; and (3) increased patient comfort. The endoscopist should appreciate these advantages and consider use of the UTCE accordingly.